The measurements of neutron Fermi Age for selected Nuclear Reactor shielding materials using the Indium foil technique - Jasim, Mahdi Hadi (Iraqi Journal of Physics, 2019)
The Neutron Fermi Age, t, and the neutron slowing down density, q (r, t) , have been measured for some materials such as Graphite and Iron by using gamma spectrometry system UCS-30 with NaI (Tl) detector. This technique was applied for Graphite and Iron materials by using Indium foils covered by Cadmium and the measurements done at the Indium resonance of 1.46 eV. These materials are exposed to a plane 241Am/Be neutron source with recent activity 38 mCi. The measurements of the Fermi Age were found to be t = 297 ± 21 cm2 for Graphite, t = 400 ± 28 cm2 for Iron. Neutron slowing down density was also calculated depending on the recent experimental t value and distance.